Marginal reef paradox: A possible refuge from environmental changes? - Soares, Marcelo de Oliveira (2019)
The occurrence of coral reef communities under extreme and different-from-optimum conditions makes it possible to test hypotheses about resilience in the face of increasing local and global impacts. Recently, coastal marginal reefs have been hypothesized to provide refugia from natural and anthropogenic impacts. Herein, I present empirical evidence contradicting this assumption and explain a new idea, called the “marginal reef paradox”. The marginal reef paradox has two main contradictory concepts. First, the hypothesis that marginal reefs may be more resilient to global changes (such as global warming and heat waves) but less resilient to local ones (such as overfishing, runoff, local pollution, dredging, river discharge, and habitat destruction). Second, that despite the resilience to thermal stress, the marginal reefs are not refugia to other reef ecosystems owing to their vulnerability and because these reefs significantly differ from their tropical counterparts. Thus, marginal reefs such as turbid-zone and high-latitude reefs are ecologically distinct ecosystems and represent limited po- tential as refugia for other reef ecosystems. I also argue that marginal reefs are under severe anthropogenic pressure and in as much need of conservation actions as “classical” coral reefs. Moreover, their resilience will be lost within the next few decades if proper and urgent conservation actions are not take